Role of Indocyanine Green in Fluorescence Imaging with Near-Infrared Light to Identify Sentinel Lymph Nodes, Lymphatic Vessels and Pathways Prior to Surgery – A Critical Evaluation of Options - Hackethal, Andreas; Hirschburger, Markus; Eicker, Sven Oliver; Mücke, Thomas; Lindner, Christoph; Buchweitz, Olaf (Geburtshilfe und Frauenheilkunde, 2018)
Modern surgical strategies aim to reduce trauma by using functional imaging to improve surgical outcomes. This reviews considers and evaluates the importance of the fluorescent dye indocyanine green (ICG) to visualize lymph nodes, lymphatic pathways and vessels and tissue borders in an interdisciplinary setting. The work is based on a selective search of the literature in PubMed, Scopus, and Google Scholar and the authorsʼ own clinical experience. Because of its simple, radiation-free and uncomplicated application, ICG has become an important clinical indicator in recent years. In oncologic surgery ICG is used extensively to identify sentinel lymph nodes with promising results. In some studies, the detection rates with ICG have been better than the rates obtained with established procedures. When ICG is used for visualization and the quantification of tissue perfusion, it can lead to fewer cases of anastomotic insufficiency or transplant necrosis. The use of ICG for the imaging of organ borders, flap plasty borders and postoperative vascularization has also been scientifically evaluated. Combining the easily applied ICG dye with technical options for intraoperative and interventional visualization has the potential to create new functional imaging procedures which, in future, could expand or even replace existing established surgical techniques, particularly the techniques used for sentinel lymph node and anastomosis imaging.
Keywords: ICG; sentinel; indocyanine green